KRISTENISASI MASYARAKAT ABORIJIN OLEH BANGSAKULIT PUTIH AUSTRALIA DAN RESISTENSI MASYARAKAT ABORJIN YANG TERGAMBAR DALAM MAYDINA, THE SHADOW, KARYA HYLLUS MARIS DAN SONIA BORG - Syam, Essy (Universitas Lancang Kuning, 2013)
The life of Aborginal people had changed since the coming of AngloCeltic people to Australian continent. One of the changes was the christianization done by those Anglo-Celtic people my malcing those Aboriginal people converted to Christian. Responding to this christianiz:ation, the Aboriginal people resisted. Besides, the Anglo-Celtic people dominated and oppressed the Aboriginal people. When they could no longer tolerate the domination and oppression, those Aboriginal people fought for their right and belief.